Preparation method of defective zirconium-based MOFs and application of defective zirconium-based MOFs in separation and purification of astaxanthin

By introducing structural defects in MOFs and adjusting the pore size and pore structure, the problem of insufficient adsorption and separation of active substances in larger molecular sizes is solved, and efficient separation and purification of astaxanthin is achieved, with significant purification effect.

CN119390993APending Publication Date: 2025-02-07DALIAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411479817.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The pore size of MOFs limits the adsorption and separation of active substances of larger molecular sizes.

Method used

By introducing structural defects, adjusting the pore size and pore structure of MOFs, optimizing the non-covalent bond interaction between MOFs and astaxanthin, thereby achieving efficient separation performance of astaxanthin.

Benefits of technology

The enrichment and separation ability of astaxanthin was significantly improved, and the purity of purified astaxanthin was increased by nearly 8.7 times. The method is simple to operate, low cost and reusable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390993A_ABST
    Figure CN119390993A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of defective zirconium-based MOFs and application of the defective zirconium-based MOFs in separation and purification of astaxanthin, and belongs to the technical field of porous materials. The preparation method of the defective zirconium-based MOFs specifically comprises the following steps: dissolving ZrCl4 and a ligand 4, 4 '-diphenyldicarboxylic acid in N, N-dimethylformamide, then adding an acetic acid regulator, obtaining a crude product d-UiO-67-X through a solvothermal method, and carrying out washing, drying and vacuum heating activation on the crude product to obtain the defective zirconium-based metal organic framework material d-UiO-67-X. According to the method disclosed by the invention, the defect d-UiO-67-X is successfully constructed through a modifier-induced defect engineering strategy, and the sizes and chemical properties of pores can be adjusted and the adsorption separation performance of the astaxanthin can be enhanced by controlling the defects, so that the astaxanthin can be effectively and selectively separated from a complex matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous materials, and specifically relates to a method for preparing defective zirconium-based MOFs and an application thereof in the separation and purification of astaxanthin. Background Art

[0002] Astaxanthin is a carotenoid found mainly in various algae, yeast and marine animals. Astaxanthin has excellent antioxidant properties, far exceeding other natural carotenoids. Due to its strong free radical scavenging ability, it has positive effects in antioxidant, anti-tumor, anti-inflammatory and cardiovascular diseases. Although synthetic astaxanthin is the cheapest and most abundant source, it is worth noting that the isomers produced by this method are limited to (3R, 3'R). Astaxanthin from natural sources exists in a mixture of three different isomers (3S, 3'S), (3R, 3'S) and (3R, 3'R), and these isomers have higher biological activity. Due to its superior biological activity, the demand for natural astaxanthin has been increasing. Natural astaxanthin can be obtained from microorganisms, such as Haematococcus pluvialis and Phaffia rhodozyma, which are being widely developed. The extraction, separation and purification of astaxanthin have also become a hot topic in current research.

[0003] Common separation and purification methods for astaxanthin include chromatography, extraction and recrystallization. Since astaxanthin will exist in the form of astaxanthin esters with fatty acids of different chain lengths in algae, it is difficult to obtain high-purity astaxanthin simply through organic solvent extraction and recrystallization. Saponification using alkaline solutions can quickly release astaxanthin and astaxanthin esters, which greatly improves the purification effect of astaxanthin. However, there are many types of impurities in Haematococcus pluvialis, with complex structures, and interference from other carotenoid components, such as fucoxanthin, chlorophyll and β-carotene, which cause great difficulties in the separation and purification of astaxanthin. The materials that have been reported to purify astaxanthin have low adsorption capacity for astaxanthin and high production costs. Therefore, it is necessary to find an efficient, low-cost and reusable separation and purification method.

[0004] Metal organic frameworks (MOFs) are organic / inorganic materials composed of metal ions or metal clusters and organic ligands. Due to their extremely high specific surface area, adjustable pore structure, high porosity and abundant functional sites, MOFs have attracted extensive attention in drug delivery, adsorption separation, chemical sensing and catalysis. Although pores play a very important role in the practical application of MOFs, the pore size of most traditional MOFs is less than 2nm, which limits their adsorption and separation of active substances with larger molecular sizes. Therefore, the present invention introduces structural defects to increase the adsorption sites while increasing the pore size, optimizes the non-covalent bond interaction between MOFs and astaxanthin, and achieves efficient separation performance of astaxanthin. Summary of the invention

[0005] [Technical issues]

[0006] The technical problem to be solved by the present invention is that the pore size of MOFs limits the adsorption and separation of active substances with larger molecular sizes.

[0007] [Technical solution]

[0008] In order to solve the above problems, the present invention provides a method for preparing defective zirconium-based MOFs, which uses defect technology to fine-tune the porous structure, thereby achieving efficient separation and purification of astaxanthin.

[0009] The present invention provides a method for preparing a defective zirconium-based metal organic framework material, comprising the following steps: ZrCl 4 It is dissolved in N,N-dimethylformamide with the ligand 4,4'-biphenyldicarboxylic acid (BPDC), and then acetic acid is added as a regulator. The crude product d-UiO-67-X is obtained by a solvothermal method. The crude product is washed, dried, and activated by vacuum heating to obtain a defective zirconium-based metal-organic framework material d-UiO-67-X.

[0010] In one embodiment of the present invention, the reaction conditions of the solvothermal method are: heating the reaction at 100-120° C. for 12-14 hours.

[0011] In one embodiment of the present invention, ZrCl 4 The molar ratio of the ligand 4,4'-biphenyldicarboxylic acid is 1:1 to 1.2.

[0012] In one embodiment of the present invention, the molar ratio of the acetic acid regulator to the ligand 4,4'-biphenyldicarboxylic acid is 2 to 8:1.

[0013] In one embodiment of the present invention, the drying is performed by vacuum heating in a vacuum drying oven at 70 to 80° C. for 12 to 14 hours.

[0014] In one embodiment of the present invention, the temperature of heating activation is 120-150° C., the activation time is 12-14 hours, and the vacuum degree is -0.1 MPa.

[0015] The present invention provides a defective zirconium-based metal organic framework material prepared by the above method.

[0016] The present invention also provides the application of the above-mentioned defective zirconium-based metal organic framework material in the field of astaxanthin separation and purification.

[0017] In one embodiment of the present invention, the steps of separating and purifying astaxanthin by defective zirconium-based metal-organic framework materials are as follows: extracting from Haematococcus pluvialis by solvent extraction to obtain a crude extract of astaxanthin with an ester group, removing the ester group on the astaxanthin by saponification reaction to obtain a saponified crude astaxanthin extract, then adding a defective zirconium-based metal-organic framework material to selectively adsorb the saponified crude astaxanthin extract, and then desorbing the astaxanthin by an eluent to achieve the effect of removing impurities and purifying astaxanthin.

[0018] [Beneficial Effects]

[0019] (1) The use of d-UiO-67-X can significantly improve the enrichment and separation capacity of astaxanthin, and this technology has the advantages of simple operation, low cost, and little secondary pollution.

[0020] (2) The zirconium-based MOFs used have excellent structural stability and are non-toxic.

[0021] (3) This method has a high separation and purification efficiency, and the adsorbent can be repeatedly used in the purification process.

[0022] (4) The method of the present invention successfully constructed defective d-UiO-67-X through a regulator-induced defect engineering strategy. By controlling the defects, the size of the pores and the chemical properties of the pores can be adjusted to enhance the adsorption and separation performance of astaxanthin. The adsorption absorption rate of astaxanthin was 1.98 mg g -1 The maximum adsorption capacity is 26.21 mg g -1 ; Effectively and selectively separate astaxanthin from complex matrices; and the purity of astaxanthin after purification by d-UiO-67-X increased from 10.22%±0.86% to 89.0%±2.3%, an increase of nearly 8.7 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a flow chart of separation and purification of astaxanthin using defective zirconium-based metal-organic framework materials;

[0024] Figure 2 It is the XRD spectra of comparative example 1 UiO-67 and examples 1 to 4 d-UiO-67-X;

[0025] Figure 3 FT-IR spectra of comparative example 1 UiO-67 and examples 1 to 4 d-UiO-67-X;

[0026] Figure 4 It is a transmission electron microscope picture of comparative example 1UiO-67 and examples 1 to 4d-UiO-67-X;

[0027] Figure 5is the thermogravimetric analysis of Example 1 UiO-67 and Examples 1 to 4 d-UiO-67-X;

[0028] Figure 6 Comparative Example 1UiO-67 and Examples 1 to 4d-UiO-67-X 1 H-NMR;

[0029] Figure 7 The N of UiO-67 in Example 1 and d-UiO-67-X in Examples 1 to 4 is 2 Adsorption-desorption isotherms;

[0030] Figure 8 The pore size distribution of the sample UiO-67 of Example 1 and the d-UiO-67-X of Examples 1 to 4;

[0031] Fig. 9 is the UV-visible absorption spectrum standard curve of astaxanthin;

[0032] Fig.10 Comparative Example 1 UiO-67 and Comparative Example 3-4d-UiO-67-C 3 and the adsorption performance of d-UiO-67-BA on astaxanthin;

[0033] Fig.11 It is the adsorption performance of astaxanthin by UiO-67 of comparative example 1 and d-UiO-67-X of examples 1 to 4;

[0034] Fig.12 is the adsorption kinetics of astaxanthin by d-UiO-67-4 in Example 2;

[0035] Fig.13 It is a comparison of the adsorption kinetics of astaxanthin by comparative example 1UiO-67 and examples 1 to 4d-UiO-67-X;

[0036] Fig.14 This is the internal diffusion model of astaxanthin of Comparative Example 1 UiO-67 and Examples 1 to 4 d-UiO-67-X;

[0037] Fig.15 Isothermal adsorption curves of astaxanthin for Comparative Example 1 UiO-67 and Examples 1 to 4 d-UiO-67-X;

[0038] Fig.16 The Langmuir model and Freundlich model of astaxanthin in comparative example 1 UiO-67 and examples 1 to 4 d-UiO-67-X;

[0039] Fig.17 is the adsorption selectivity of astaxanthin by d-UiO-67-4 in Example 2;

[0040] Fig.18 It is the desorption performance of astaxanthin of Comparative Example 1UiO-67 and Examples 1 to 4d-UiO-67-X;

[0041] Fig.19 is the dynamic adsorption-desorption curve of astaxanthin by d-UiO-67-4 in Example 2;

[0042] Fig. 20 This is the HPLC spectrum of purified astaxanthin;

[0043] Fig.21 This is the high-resolution mass spectrum of purified astaxanthin;

[0044] Fig. 22 This is the astaxanthin adsorption-desorption repeatability of Example 2d-UiO-67-4. DETAILED DESCRIPTION

[0045] Example 1

[0046] A method for preparing a defective zirconium-based metal organic framework material comprises the following steps:

[0047] 52.9 mg of ZrCl 4 , and 55 mg of 4,4'-biphenyldicarboxylic acid were ultrasonically dissolved in 5 mL of N,N-dimethylformamide, 7.6 μL of glacial acetic acid (the molar ratio of acetic acid to ligand was 2:1, respectively) was added, and stirred at 500 rpm for 2 h at room temperature. The mixed solution was sealed in a Schott vial and ultrasonicated for 5 to 10 min until the precipitate was completely dissolved; the Schott vial containing the mixed solution was placed in an oven by a solvothermal method and reacted at 120 ° C for 12 h; after the reaction was completed, centrifuged at 5000 rpm for 5 min, and the precipitate was immersed in 5 mL of DMF and soaked for 8 h. , centrifuged at 5000rpm for 5min, added 5mL of DMF for washing again, repeated three times, after DMF washing, immersed the precipitate obtained after centrifugation in 5mL of methanol, soaked for 8h, centrifuged at 5000rpm for 5min, added 5mL of methanol for washing again, repeated three times, and then vacuum dried at 70℃ in a vacuum drying oven for 12h, and finally placed in a vacuum oven for heating activation, the vacuum degree is -0.1Mpa, the activation temperature is 150℃, and the activation time is 12h, to obtain a preparation method of a defective zirconium-based metal organic framework material, named d-UiO-67-2.

[0048] Example 2

[0049] A method for preparing a defective zirconium-based metal-organic framework material is consistent with Example 1, with the only difference being that the amount of glacial acetic acid added is 15.2 μL, that is, the molar ratio of acetic acid to the ligand is 4:1, thereby obtaining a method for preparing a defective zirconium-based metal-organic framework material, named d-UiO-67-4.

[0050] Example 3

[0051] A method for preparing a defective zirconium-based metal-organic framework material is consistent with Example 1, with the only difference being that the amount of glacial acetic acid added is 22.8 μL, that is, the molar ratio of acetic acid to the ligand is 6:1, thereby obtaining a method for preparing a defective zirconium-based metal-organic framework material, named d-UiO-67-6.

[0052] Example 4

[0053] A method for preparing a defective zirconium-based metal-organic framework material is consistent with Example 1, with the only difference being that the amount of glacial acetic acid added is 30.4 μL, that is, the molar ratio of acetic acid to the ligand is 8:1, thereby obtaining a method for preparing a defective zirconium-based metal-organic framework material, named d-UiO-67-8.

[0054] Comparative Example 1

[0055] 52.9 mg of ZrCl 4 , and 55 mg of 4,4'-biphenyldicarboxylic acid were ultrasonically dissolved in 5 mL of N,N-dimethylformamide, stirred at 500 rpm for 2 h at room temperature, the mixed solution was sealed in a Schott vial, and ultrasonicated for 5 to 10 min until the precipitate was completely dissolved; after mixing evenly, reacted in an oven at 120°C for 12 h, after the reaction was completed, centrifuged at 5000 rpm for 5 min, the precipitate obtained after centrifugation was immersed in 5 mL of DMF, soaked for 8 h, centrifuged at 5000 rpm for 5 min, and then 5 mL of DMF was added again for washing, and repeated three times. After washing with DMF, the precipitate obtained after centrifugation was immersed in 5 mL of methanol, soaked for 8 h, centrifuged at 5000 rpm for 5 min, and then 5 mL of methanol was added again for washing, and repeated three times; then dried at 70°C for 12 h to obtain the zirconium-based metal organic framework material UiO-67.

[0056] Comparative Example 2

[0057] The preparation method of a defective zirconium-based metal organic framework material is consistent with that in Example 1, except that the amount of acetic acid added is 38 μL, that is, the molar ratio of acetic acid to ligand is 10:1.

[0058] Comparative Example 3

[0059] A preparation method of a defective zirconium-based metal organic framework material is consistent with Example 1, except that acetic acid is replaced by an equal amount of propionic acid, and is named d-UiO-67-C 3 .

[0060] Comparative Example 4

[0061] The preparation method of a defective zirconium-based metal organic framework material is consistent with that in Example 1, except that acetic acid is replaced by an equal amount of benzoic acid, and the material is named d-UiO-67-BA.

[0062] Characterization of the defective zirconium-based metal organic framework material d-UiO-67-X of the present invention:

[0063] The crystal structures of UiO-67 and d-UiO-67-X were determined by X-ray diffractometer (XRD) (Shimadzu XRD-7000S, Shimadzu, Japan) in the range of 2θ values ​​of 5–50° at a scanning speed of 8° / min. Figure 2 As shown, all diffraction peaks are consistent with the XRD pattern of the standard sample, indicating that the modified material with the same topological structure as the original UiO-67 was successfully synthesized.

[0064] The structures of UiO-67 and d-UiO-67-X were analyzed by Fourier transform infrared spectroscopy (FTIR) (Spectrum two, PerkinElmer Instrument Co., Ltd., Japan), and the structure of the ligand BPDC was also analyzed. According to previous studies, UiO-67, d-UiO-67-X, and BPDC were mixed with KBr and then compressed into thin sheets. The samples were concentrated at 4000–400 cm -1 The analysis is performed within a wavenumber range. Figure 3 As shown in the figure, compared with BPDC, the -COOH stretching vibration peaks of UiO-67 and d-UiO-67-X disappeared, indicating that the Zr ion was successfully coordinated with BPDC. Compared with UiO-67, the asymmetric and symmetric stretching vibration peaks of COO- of d-UiO-67-X were red-shifted. This may be due to the partial substitution of the BPDC ligand by the acetate monocarboxylic acid regulator in the structure.

[0065] Transmission electron microscopy (TEM) images were collected using a JEM-2100 (UHR) instrument, such as Figure 4 As shown, UiO-67 has obvious particle agglomeration phenomenon, and the morphology of d-UiO-67-X is clear octahedral crystal particles.

[0066] Thermogravimetric analysis (TGA) was performed using a thermogravimetric analyzer (TGA-550) in a temperature range of 30–800 °C and a heating rate of 10 °C min-1 in a nitrogen atmosphere. -1 .like Figure 5As shown in the figure, the BPDC decomposition weight loss of d-UiO-67-X is smaller (37.65%) compared with UiO-67. At 400-600 °C, the BPDC decomposition weight loss of d-UiO-67-2, d-UiO-67-4, d-UiO-67-6 and d-UiO-67-8 are 37.63%, 36.98%, 36.80% and 33.36%, respectively. This indicates that the absence of BPDC linker increases by increasing the amount of acetate modifier in the structure.

[0067] 1 The H-NMR spectrum was determined using a Bruker AVANCE III (400 MHz) spectrometer. The optimized sample digestion procedure was as follows: 18 mg of sample and 23 mg of NaOH were added, followed by 0.55 mL of D 2 O, and sonicate several times until the solution is clear. Figure 6 As shown in Figure 2, all d-UiO-67-X have two significant signals in the 1H NMR spectrum, namely BPDC (δ = 7.85 and 7.60 ppm, 8H) and acetic acid (δ = 1.84 ppm, 3H). 1 The integrated area of ​​the H-NMR peaks showed that the molar ratio of acetic acid / BPDC increased with the increase of the amount of acetic acid used in the synthesis, indicating that more defect sites were formed by the addition of acetic acid modulator in the structure.

[0068] The Brunauer–Emmett–Teller surface area of ​​the samples was measured by a multi-station BET analyzer (Micromeritics ASAP 2460). Figure 7 As shown, the N of UiO-67 and d-UiO-67-X 2 The adsorption-desorption isotherm is a typical type i isotherm for microporous materials.

[0069] The pore size distribution of the samples was measured by a multi-station BET analyzer (Micromeritics ASAP 2460). Figure 8 As shown, the pore size distribution of UiO-67 shows that the maximum pore size is at 0.7 nm, while the pore size of d-UiO-67-X increases significantly at ∼1.25 nm, and the pore size expands to 1.7–2.1 nm.

[0070] The separation and purification performance of the defective zirconium-based metal organic framework material of the present invention on astaxanthin:

[0071] (1) d-UiO-67-4, d-UiO-67-C 3 Adsorption performance of astaxanthin with d-UiO-67-BA

[0072] Standard astaxanthin (purchased from Shanghai MacLean Reagent Co., Ltd.) was dissolved in acetone to prepare 2, 4, 5, 6, and 8 mg / L astaxanthin-acetone solutions. The absorbance of astaxanthin was measured in the range of 350-700 nm using an SP-2500 UV-visible spectrophotometer, with acetone as the blank. Fig. 9 As shown, the concentration was 2 to 8 mg L -1 Standard curve of astaxanthin solution.

[0073] Standard astaxanthin was dissolved in acetone to prepare 8 mg / L astaxanthin-acetone solution. A typical adsorption experiment was performed by adding 10 mg of d-UiO-67-4, d-UiO-67-C 3 Add d-UiO-67-BA to 5 mL of astaxanthin-acetone solution and let it stand in the astaxanthin-acetone solution for adsorption. After a certain adsorption time, take the supernatant to measure the UV-visible absorption spectrum and compare it with the UV-visible absorption spectrum before adsorption of astaxanthin. Then pour the supernatant back to continue adsorption. The adsorption amount q at a certain time t t Determined by the following formula:

[0074]

[0075] In the formula, C 0 , C t and C e (mg L -1 ) are the initial astaxanthin concentration in the solution, the concentration at a certain time t and the end of adsorption, V(L) is the volume of the solution, and m(g) is the mass of the added adsorbent.

[0076] The absorbance of astaxanthin was measured in the range of 350-700 nm using a SP-2500 UV-visible spectrophotometer, with acetone as blank. Fig.10 As shown in Figure 2, the adsorption rate of astaxanthin by d-UiO-67-4 was 3.63 mg g -1 , significantly higher than d-UiO-67-C 3 (3.50mg g -1 ) and d-UiO-67-BA (3.24 mg g -1 ). Therefore, compared with the adsorption rate and adsorption capacity of the other three d-UiO-67-X materials, d-UiO-67-4 exhibits the best adsorption performance.

[0077] (2) Adsorption performance of UiO-67 and d-UiO-67-X on astaxanthin

[0078] Dissolve standard astaxanthin in acetone to prepare a 4 mg / L astaxanthin-acetone solution. Using a typical adsorption experiment, add 10 mg of adsorbent d-UiO-67-X to 5 mL of astaxanthin-acetone solution and let it stand for adsorption in the astaxanthin-acetone solution. After a certain adsorption time, take the supernatant to measure the UV-visible absorption spectrum and compare it with the UV-visible absorption spectrum before adsorption of astaxanthin. Then pour the supernatant back to continue adsorption.

[0079] The absorbance of astaxanthin was measured in the range of 350-700 nm using a SP-2500 UV-visible spectrophotometer, with acetone as blank. Fig.11 As shown in Figure 2, the adsorption rate of astaxanthin by UiO-67 was 0.96 mg g -1 , which is significantly lower than that of d-UiO-67-X. In addition, when the molar ratio of acetic acid to BPDC increased from 2 to 4, the adsorption amount of astaxanthin increased from 1.87 mg g in d-UiO-67-2 to 1.5 mg g in d-UiO-67-X. -1 Increased to 1.98 mg g in d-UiO-67-4 -1 When the ratio of acetic acid to BPDC was further increased to 6 and 8, the adsorption of astaxanthin on d-UiO-67-6 and d-UiO-67-8 decreased to 1.86 and 1.66 mg g, respectively. -1 Therefore, compared with the adsorption rate and adsorption capacity of the other three d-UiO-67-X materials, d-UiO-67-4 exhibited the best adsorption performance.

[0080] (2) Adsorption kinetics of astaxanthin on d-UiO-67-4

[0081] Dissolve standard astaxanthin in acetone to prepare 2, 4, and 8 mg / L astaxanthin-acetone solutions. Using a typical adsorption experiment, add 10 mg of adsorbent to 5 mL of astaxanthin-acetone solution. The sample is allowed to stand in the astaxanthin solution for adsorption. After a certain adsorption time, take the supernatant to measure the UV-visible absorption spectrum and compare it with the UV-visible absorption spectrum before adsorption of astaxanthin. Then pour the supernatant back to continue adsorption.

[0082] The adsorption kinetics of astaxanthin on defective UiO-67 at three different concentrations were evaluated using pseudo-first-order and pseudo-second-order models:

[0083] ln(q e -q t )=lnq e -k 1 t

[0084]

[0085] where q t and qe (mg g -1 ) are the amount of anthocyanins adsorbed at a certain time t and equilibrium time, respectively, k 1 (min -1 ) and k 2 (gmg -1 min -1 ) are the rate constants of the pseudo-first-order and pseudo-second-order models, respectively.

[0086] The absorbance of astaxanthin was measured in the range of 350-700 nm using a SP-2500 UV-visible spectrophotometer, with acetone as the blank.

[0087] like Fig.12 As shown, compared with the pseudo-first-order model, the different astaxanthin concentrations (2, 4 and 8 mg L -1 The R value of the d-UiO-67-4 pseudo-second-order model fitting data 2 The coefficient is higher. This indicates that the adsorption process of astaxanthin by d-UiO-67-4 is mainly controlled by chemical adsorption.

[0088] (3) Comparison of adsorption kinetics of astaxanthin between UiO-67 and d-UiO-67-X

[0089] Dissolve standard astaxanthin in acetone to prepare 2, 4, and 8 mg / L astaxanthin-acetone solutions. Using a typical adsorption experiment, add 10 mg of adsorbent to 5 mL of astaxanthin-acetone solution. The sample is allowed to stand in the astaxanthin solution for adsorption. After a certain adsorption time, take the supernatant to measure the UV-visible absorption spectrum and compare it with the UV-visible absorption spectrum before adsorption of astaxanthin. Then pour the supernatant back to continue adsorption.

[0090] The adsorption kinetics of astaxanthin on defective UiO-67 at three different concentrations were evaluated using pseudo-first-order and pseudo-second-order models:

[0091] ln(q e -q t )=lnq e -k 1 t

[0092]

[0093] where q t and q e (mg g -1 ) are the amount of anthocyanins adsorbed at a certain time t and equilibrium time, respectively, k 1 (min -1 ) and k 2 (gmg -1 min -1) are the rate constants of the pseudo-first-order and pseudo-second-order models, respectively.

[0094] The absorbance of astaxanthin was measured in the range of 350-700 nm using a SP-2500 UV-visible spectrophotometer, with acetone as the blank.

[0095] like Fig.13 As shown in the figure, compared with UiO-67, d-UiO-67-X has a stronger adsorption effect on astaxanthin than UiO-67, and the adsorption process is mainly controlled by chemical adsorption.

[0096] (4) Internal diffusion model of astaxanthin in UiO-67 and d-UiO-67-X

[0097] Dissolve standard astaxanthin in acetone to prepare 2, 4, and 8 mg / L astaxanthin-acetone solutions. Using a typical adsorption experiment, add 10 mg of adsorbent to 5 mL of astaxanthin-acetone solution. The sample is allowed to stand in the astaxanthin solution for adsorption. After a certain adsorption time, take the supernatant to measure the UV-visible absorption spectrum and compare it with the UV-visible absorption spectrum before adsorption of astaxanthin. Then pour the supernatant back to continue adsorption.

[0098] The intra-particle diffusion kinetic model adopts the following formula:

[0099] q t =k i t 0.5 +C i

[0100] Where k i is the intraparticle diffusion kinetic adsorption constant (nmol g -1 min 0.5 ), C i is the intercept of the linear curve.

[0101] like Fig.14 As shown, the slopes of all d-UiO-67-X in the first and second stages are significantly higher than those of UiO-67, indicating that the increase in pore size and BET specific surface area caused by the defective structure promotes the high diffusion of astaxanthin in the pores of d-UiO-67-X. In addition, by comparing the slopes of the two stages, the slope of the first stage is significantly higher than that of the second stage. This can be explained as follows: at the beginning of adsorption, there are enough adsorption active sites to interact with astaxanthin. At the same time, the diffusion of astaxanthin has a large accessible pore volume. When most of the adsorption sites and pore volume are occupied by astaxanthin, the adsorption diffusion rate is bound to decrease.

[0102] (5) Isothermal adsorption curves of astaxanthin on UiO-67 and d-UiO-67-X

[0103] Dissolve standard astaxanthin in acetone to prepare 2-56 mg / L astaxanthin-acetone solution. Using a typical adsorption experiment, add 10 mg of adsorbent to 5 mL of astaxanthin-acetone solution. The sample is allowed to stand in the astaxanthin solution for adsorption. After a certain adsorption time, take the supernatant to measure the UV-visible absorption spectrum.

[0104] like Fig.15 As shown in Figure 2, with the increase of astaxanthin concentration, the adsorption amount of d-UiO-67-X and UiO-67 increased accordingly. -1 The adsorption reaches saturation when the adsorption capacity of d-UiO-67-4 is 26.21 mg g -1 , which is significantly higher than that of UiO-67 (7.22 mg g -1 ) and other three d-UiO-67-X (20.46~22.62mg g -1 ).

[0105] (6) Langmuir model and Freundlich model of astaxanthin in UiO-67 and d-UiO-67-X

[0106] Dissolve standard astaxanthin in acetone to prepare 2-56 mg / L astaxanthin-acetone solution. Using a typical adsorption experiment, add 10 mg of adsorbent to 5 mL of astaxanthin-acetone solution. The sample is allowed to stand in the astaxanthin solution for adsorption. After a certain adsorption time, take the supernatant to measure the UV-visible absorption spectrum.

[0107] The adsorption isotherms were analyzed using the linear Langmuir and Freundlich isotherm models. The applied formulas for these models are as follows:

[0108]

[0109] Where K L and K F represent the Langmuir constant and the Freundlich constant respectively; Q e (mg g -1 ) is the equilibrium adsorption capacity; C e (mg L -1 ) represents the equilibrium concentration of astaxanthin solution; Q m (mg g -1 ) is the maximum adsorption capacity; 1 / n is a dimensionless empirical constant reflecting the intensity of the adsorption process.

[0110] like Fig.16As shown in Figure 2, the Freundlich and Langmuir isotherm models are fitted to the adsorption isotherm of d-UiO-67-X. The Freundlich model fits the data R 2 The higher coefficient indicates the existence of multilayer adsorption on the heterogeneous surface.

[0111] (7) Adsorption selectivity of d-UiO-67-4 for astaxanthin

[0112] Astaxanthin, fucoxanthin, lutein, lycopene, β-carotene and chlorophyll were dissolved separately to prepare a 4 mg / L solution. A typical adsorption experiment was used to add 10 mg of the adsorbent to 5 mL of the solution. The sample was allowed to stand in the solution for adsorption. At a certain adsorption time, the supernatant was taken to measure the UV-visible absorption spectrum and compared with the UV-visible absorption spectrum before adsorption.

[0113] like Fig.17 As shown, the adsorption efficiency of fucoxanthin (51.06%) and lutein (58.29%) was higher than that of lycopene (3.92%), β-carotene (3.17%) and chlorophyll (2.96%), but still significantly lower than that of astaxanthin (98.14%).

[0114] (8) Desorption performance of astaxanthin by UiO-67 and d-UiO-67-X

[0115] 10 mg of d-UiO-67-X with different defects was weighed and 5 mL of 4 mg / L astaxanthin solution was added. When the adsorbent reached adsorption equilibrium, it was washed with acetone 2-3 times. Then, 5 mL of 4% acetic acid-acetone solution, 75% ethanol, DMSO, ethyl acetate and n-hexane solution were used for desorption and ultrasonic treatment for 30 minutes. After centrifugation, the supernatant was taken and the desorption content of astaxanthin was determined by UV-visible absorption spectroscopy. The equilibrium experiment was repeated three times, and the desorption rate of five desorbents was calculated.

[0116] The desorption rate is calculated by the following formula:

[0117]

[0118] In the formula, C 0 and C d (mg L -1 ) are the initial astaxanthin concentration and the astaxanthin concentration after desorption, respectively.

[0119] like Fig.18As shown, elution solvents of different polarities have a great influence on the release rate of astaxanthin from d-UiO-67-X. When a mixture of 75% ethanol and 25% water is used, the release rate of astaxanthin in d-UiO-67-4 is the highest (72.41%) compared with other elution solvents. It should be noted that the water content in ethanol (0-45%) has a great influence on the release effect. When only ethanol is used as the elution solvent, the release amount of astaxanthin is extremely low (~11.22-12.66%). The astaxanthin release rate of 75% ethanol-25% water mixture for d-UiO-67-2, d-UiO-67-4 and d-UiO-67-6 is higher than that of ethanol-water mixtures with other ratios. This may be due to the fact that the addition of 75% ethanol-25% water effectively destroyed the polarity balance and intermolecular interactions between d-UiO-67-4 and astaxanthin, thereby enabling the release of astaxanthin from d-UiO-67-4.

[0120] (9) Dynamic adsorption-desorption curve of astaxanthin on d-UiO-67-4

[0121] S1. Extract astaxanthin by solvent extraction. Place Haematococcus pluvialis powder (500 mg) in a beaker and add 10 mL of dichloromethane. After mixing evenly, use an ultrasonic cell disruptor to ultrasonically disrupt for 5 minutes at 500 W, then stir and extract for 40 minutes. After centrifugation to remove the supernatant, add new extraction solution and extract repeatedly for 4 times until the filtrate becomes light color. Then remove the solvent by rotary evaporation to obtain a crude astaxanthin extract with an ester group.

[0122] S2. Weigh the crude extract, add anhydrous ethanol to ultrasonically dissolve it, and then centrifuge to remove impurities. Then use a 0.45 μm organic phase filter to further remove impurities. Adjust the pH to 10 with 10% KOH-ethanol solution, saponify it in a refrigerator at 4°C for 12 hours, and then adjust the pH to neutral with 10% dilute hydrochloric acid. Freeze-dry to obtain the saponified astaxanthin crude extract.

[0123] S3. Column chromatography experiments use an EZ-type gravity column (d=9.56mm and l=55mm), and fill the column with 200mg of the selected adsorbent. First, rinse the adsorbent with 20mL of ethanol through a peristaltic pump (LHZW005XT) until the effluent is colorless. Then, a 30mg / L saponified crude astaxanthin solution is pumped into the chromatography column at a flow rate of 0.25mL / min through a peristaltic pump. During the adsorption process, 5mL of effluent is collected at regular intervals, and the absorbance of residual astaxanthin in the effluent is detected at 480nm by UV-visible spectroscopy. Until the absorbance of astaxanthin in the effluent is equal to that of the initial solution. With the adsorption time as the horizontal coordinate and the absorbance ratio of astaxanthin in the effluent solution to the initial solution as the vertical coordinate, a dynamic adsorption curve is drawn.

[0124] S4. When adsorption equilibrium is reached, stop injecting. Pass 20 mL of deionized water and 20 mL of ethanol for washing. Then pass 60% ethyl acetate-ethanol solution for desorption, the flow rate is 0.5 mL / min, collect a tube of effluent every 5 mL, and detect the absorbance of residual astaxanthin in the effluent at 480 nm by UV-visible spectroscopy until the peak representing astaxanthin in the effluent disappears. Draw a dynamic desorption curve with the adsorption time as the horizontal coordinate and the absorbance of astaxanthin in the effluent water as the vertical coordinate.

[0125] like Fig.19 As shown, by plotting a / A 0 Breakthrough adsorption curve with adsorption time. Breakthrough time (t b ) and exhaustion time (t e ) indicates the time when the effluent astaxanthin concentration reaches 10% and 90% of the initial astaxanthin concentration. d-UiO-67-4 has the longest depletion time (about 1050 min), and d-UiO-67-8 has the fastest depletion time (about 870 min). It can be seen from the dynamic desorption curve that the absorbance of astaxanthin in the eluate increases rapidly at the beginning, and as the desorption time increases, the desorbed astaxanthin gradually decreases.

[0126] (10) Separation and purification performance of d-UiO-67-4 adsorbent for astaxanthin

[0127] The saponified astaxanthin extract (20 μl) was analyzed at 25°C using an Elite Hypersil C18 column (250 mm × 4.6 mm × 5 μm). The mobile phase was solvent A (dichloromethane / methanol / acetonitrile / water, 5.0:85.0:5.5:4.5, v / v) and solvent B (dichloromethane / methanol / acetonitrile / water, 22.0:28.0:45.5:4.5, v / v). After the solution was filtered through a 0.22 μm microporous membrane, HPLC analysis was performed using the following gradient program: 100% B, 0-8 min; 100% A, 8-20 min. The flow rate was 1.0 mL / min. The peak astaxanthin was measured at a wavelength of 480 nm, and the chromatographic peak was determined by comparing the retention time and spectrum with the astaxanthin standard.

[0128] like Fig. 20As shown, free astaxanthin with a purity of 10.22% was isolated from Haematococcus pluvialis. According to HPLC-UV analysis, the purity of saponified astaxanthin can reach 48.6%. This indicates that many impurities containing inorganic salts, fatty acids and other extracted carotenoids still exist in the saponified astaxanthin product. The separation and purification performance of astaxanthin by d-UiO-67-4 adsorbent was evaluated. The astaxanthin released after purification by d-UiO-67-4 has an adsorption peak at 480nm with a retention time of 1.78min, which is consistent with the HPLC spectrum of standard astaxanthin (retention time of 1.78min). According to HPLC-UV analysis, the purity of astaxanthin purified by d-UiO-67-4 increased from 10.22%±0.86% to 89.0%±2.3%, and the purity increased by nearly 8.7 times.

[0129] The astaxanthin released from d-UiO-67-4 was characterized by atmospheric pressure chemical ionization tandem mass spectrometry (APCI-MS).

[0130] like Fig.21 As shown in the figure, in the positive ionization mode, the astaxanthin detected is an ion with a mass-to-charge ratio (m / z) of 597.39. The detection result is consistent with that of standard astaxanthin.

[0131] (11) Adsorption-desorption cycle of astaxanthin by d-UiO-67-4 adsorbent

[0132] Weigh 10 mg of d-UiO-67-4 sample and add 5 mL of 56 mg / L astaxanthin solution. When the adsorbent reaches adsorption equilibrium, the adsorption amount of astaxanthin is detected by UV-visible absorption spectroscopy. Then add 5 mL of desorption solution for desorption. The adsorption-desorption process is repeated five times. The repeatability of the d-UiO-67-4 adsorbent is determined by comparing the adsorption content of astaxanthin by the adsorbent each time.

[0133] like Fig. 22 As shown, after five adsorption-desorption recovery experiments, the adsorption amount of d-UiO-67-4 only decreased by 12.14%, indicating that the material has good stability.

[0134] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing a defective zirconium-based metal-organic framework material, characterized in that: The following steps are involved: ZrCl4 and the ligand 4,4'-biphenyldicarboxylic acid are dissolved in N,N-dimethylformamide, and then acetic acid is added as a regulator. The crude product d-UiO-67-X is obtained by a solvothermal method. The crude product is washed, dried, and activated by vacuum heating to obtain a defective zirconium-based metal-organic framework material d-UiO-67-X.

2. The method for preparing a defective zirconium-based metal-organic framework material according to claim 1, characterized in that: The molar ratio of ZrCl4 to the ligand 4,4'-biphenyldicarboxylic acid is 1:1 to 1.

2.

3. The method for preparing a defective zirconium-based metal-organic framework material according to claim 1, characterized in that: The molar ratio of the acetic acid regulator to the ligand 4,4'-biphenyldicarboxylic acid is 2 to 8:

1.

4. The method for preparing a defective zirconium-based metal-organic framework material according to claim 1, characterized in that: The molar ratio of the acetic acid regulator to the ligand 4,4'-biphenyldicarboxylic acid is 4:

1.

5. The method for preparing a defective zirconium-based metal-organic framework material according to claim 1, characterized in that: The conditions of the solvothermal method are: heating the reaction at 100-120°C for 12-14 hours.

6. The method for preparing a defective zirconium-based metal-organic framework material according to claim 1, characterized in that: Drying is carried out by vacuum heating in a vacuum drying oven at 70-80°C for 12-14 hours.

7. The method for preparing a defective zirconium-based metal-organic framework material according to claim 1, characterized in that: The temperature of vacuum heating activation is 120-150°C.

8. The method for preparing a defective zirconium-based metal-organic framework material according to claim 1, characterized in that: The activation time of vacuum heating activation is 12 to 14 hours.

9. A defective zirconium-based metal organic framework material prepared by the method according to any one of claims 1 to 8.

10. Use of the defective zirconium-based metal organic framework material according to claim 9 in the field of astaxanthin separation and purification.

Citation Information

Cited By

  • Mesoporous metal organic framework-based astaxanthin selective separation and purification method

    CN120794894A